2013
DOI: 10.1186/1750-1326-8-25
|View full text |Cite
|
Sign up to set email alerts
|

LRP1 is critical for the surface distribution and internalization of the NR2B NMDA receptor subtype

Abstract: BackgroundThe N-methyl-D-aspartate receptors are key mediators of excitatory transmission and are implicated in many forms of synaptic plasticity. These receptors are heterotetrameres consisting of two obligatory NR1 and two regulatory subunits, usually NR2A or NR2B. The NR2B subunits are abundant in the early postnatal brain, while the NR2A/NR2B ratio increases during early postnatal development. This shift is driven by NMDA receptor activity. A functional interplay of the Low Density Lipoprotein Receptor Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…However, recent studies have shown that LRP1 may exert biological functions beyond cellular uptake and cargo transport (May et al, 2007). LRP1 is abundantly expressed in neurons (May et al, 2004;Liu et al, 2011;Ruzali et al, 2012;Maier et al, 2013), and it has been shown to trans-activate Trk receptors through Src family kinase (SFK) activation and signaling, leading to the activation of Akt and to neurite outgrowth (Shi et al, 2009). By showing that knocking down endogenous LRP1 leads to caspase-3 activation and increased neuronal apoptosis, Fuentealba et al (2009) demonstrated that LRP1 plays a pivotal role in the survival of primary neurons under different stress conditions such as trophic withdrawal, the presence of apoptosis inducers, or amyloid-beta-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that LRP1 may exert biological functions beyond cellular uptake and cargo transport (May et al, 2007). LRP1 is abundantly expressed in neurons (May et al, 2004;Liu et al, 2011;Ruzali et al, 2012;Maier et al, 2013), and it has been shown to trans-activate Trk receptors through Src family kinase (SFK) activation and signaling, leading to the activation of Akt and to neurite outgrowth (Shi et al, 2009). By showing that knocking down endogenous LRP1 leads to caspase-3 activation and increased neuronal apoptosis, Fuentealba et al (2009) demonstrated that LRP1 plays a pivotal role in the survival of primary neurons under different stress conditions such as trophic withdrawal, the presence of apoptosis inducers, or amyloid-beta-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lrp1 interacts with the N-methyl-D-aspartate receptor (NMDAR), promoting the endocytosis of NMDAR from the cell surface [19]. Additionally, loss of Lrp1 hinders some elements of NMDAR signaling, such as internalization of GluA1 and degradation of PSD-95 [20].…”
Section: Reelin Apoe Receptors and Glutamate Signalingmentioning
confidence: 99%
“…Also, the expression of LRP1 in radial glia of the adult spinal cord and the involvement of LRP1 in neuroblast migration along the rostral-migratory stream has recently been reported (Petit et al 2011; Rabiej et al 2016). Furthermore, LRP1 is responsible for amyloid precursor protein (APP)-transport and post-synaptic receptor trafficking, which underlines its essential function in the adult brain (Jaeger and Pietrzik 2008; Maier et al 2013). …”
Section: Introductionmentioning
confidence: 99%